A New Condition of Formation and Stablity of All Crystalline Systems in a Good Agreement with Experimental Data (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this paper we derived a new condition of formation and stability of all crystalline systems and we checked its validity and it is found to be in a good agreement with experimental data. This condition is derived directly from the quantum conditions on the free electron Fermi gas inside the crystal. The new condition relates both the volume of Fermi sphere VF and volume of Brillouin zone VB by the valence electron concentration VEC as ; for all crystalline systems (where n is the number of atoms per lattice point).